2022
DOI: 10.3390/plants11030464
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Technologies for American Chestnut (Castanea dentata (Marshall) Borkh) Conservation

Abstract: American chestnut (Castanea dentata), a native species of eastern North America, is an economically important deciduous hardwood tree that has been designated as endangered in Canada. The population of American chestnut trees has dwindled significantly across Southern Ontario due to chestnut blight and many of the surviving trees continue to show blight disease symptoms. American chestnut requires efficient strategies for propagation and preservation for species recovery. The objective of this study was to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
(152 reference statements)
0
9
0
Order By: Relevance
“…WPM is the most commonly used basal culture medium for woody plants (Liu et al, 2022). Among the Hydrangeaceae family, micropropagation studies of two Hydrangea macrophylla cultivars have been reported, and the explants were cultured on B5 basal culture medium (Khaing et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…WPM is the most commonly used basal culture medium for woody plants (Liu et al, 2022). Among the Hydrangeaceae family, micropropagation studies of two Hydrangea macrophylla cultivars have been reported, and the explants were cultured on B5 basal culture medium (Khaing et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, there are relatively few reports of successful cryopreservation using shoot tips of woody tropical species, but survival of 70% or more following cryopreservation has been reported for Parkia speciosa, Trichilia emetica, Carica papaya, Citrus aurantium, Citrus suavissima and Manihot esculenta [124]. Shoot tips from in vitro cultures have been also been used to cryopreserve the fungal-blight affected Castanea dentata (Fagaceae) [131]. Application of antioxidants such as vitamins C and E during pretreatment and recovery may help to increase survival and regrowth after cryopreservation of both shoot tips [132] and seed embryonic axes [133].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Genus, it completely surrounds the fruit or fruits of the recurrent type, the number of which ranges from 1-3, and has 2-4 leaves. When the cupula matures, it opens through these flaps (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%